Numerical Analysis of a New Type of Dishwasher Pump for Different Rotation Speeds of the Volute - Ning, Chao; Li, Yalin; Huang, Ping; Xu, Hui; Zheng, Feng (Frontiers in Energy Research, 2022)
The interaction between impeller and volute produces a complex and unsteady water flow. It involves the interference of the non-uniform flow (such as the impeller’s jet wake and a secondary flow). In this paper, the transient flow in a new type of dishwasher pump is investigated numerically. In addition, pressure measurements are used to validate the numerical method, and the simulation results agree well with the experiment. Three schemes, 0 rpm (revolutions per minute)/30 rpm/60 rpm, of volute speeds are investigated. Multiple monitoring points are set at different positions of the new dishwasher pump to record pressure-pulse signals. In addition, frequency signals are obtained using a Fast Fourier Transform, which is then used to analyze the effect of the volute tongue and the outflow of the impeller. The radial force on the principal axis is recorded, and the schemes with different rotation speeds of volute are compared. The results show that the volute speed has only a small effect on the pump performance. In addition, the speed of the volute mainly affects the flow field in the transition section located between impeller and volute. The difference of the flow field in the impeller depends on the relative position between the impeller and the volute. The time domain curve for the pressure pulse is periodic, and there is a deviation between the peak for the schemes in the outflow region. In the frequency domain, the characteristic frequency equals the blade passing frequency. In the outflow region, the effect of the volute speeds increases with increasing volute speed. For the radial force, the rotating volute strengthens the fluctuation of the radial force, which affects the operational stability of the pump. The shape of the vector distribution is most regular for the 30 rpm scheme, which indicates that the stability of the pump is the highest. This paper can be used to improve both the control and selection of volute speeds.